Infant and young child feeding practices: a cross sectional study in Sikkim - Reddy, Ravichandra; Subba, Gangaraj; Dutta, Sudip (International Journal of Contemporary Pediatrics, 2016)
Background:Positive parental attitudes towards infant feeding are an important component in child nutritional health. The nutritional well-being of a population is both an outcome and an indicator of national development. Nutrition is therefore, an issue of survival, health and development for current and succeeding generations. The purpose of the study was to assess the breast feeding & complementary feeding practices in children between the age group of 6 months-5 years, to determine the nutritional status of children less than 5 years. Methods: Children between 6 months-5 years who fulfilled the inclusion criteria’s were studied and analysed. Results:98.0% of the children has received breast fed and 72.5% of cases received exclusive breastfed till 6 months of age. 72.5% of children received complementary feed at 6 months of age appropriately but formula feed was seen in 99.0%. 46.0% of mother used bottle for feeding although literacy among 90.0% of mothers seen. Conclusions:This study has shown that existence of using bottle for feeding although the most of their mothers were educated with high breastfed rate.